Switchable dispersive liquid–liquid microextraction for lead enrichment: a green alternative to classical extraction techniques. Issue 4 (8th January 2016) - Naeemullah,; Shah, Faheem; Kazi, Tasneem Gul; Afridi, Hassan Imran; Khan, Abdur Rahman; Arain, Sadaf Sadia; Arain, Mariam Shahzadi; Panhwar, Abdul Haleem
Abstract : Switchable dispersive liquid–liquid microextraction (SDLLME): A new tool for the extraction of trace Pb. Abstract : A new, innovative and green switchable dispersive liquid–liquid microextraction (SDLLME) method has been introduced as a preconcentration tool for the removal of the toxic metal lead (Pb) in fresh and waste water samples prior to determination with flame atomic absorption spectrometry. We developed a switchable polarity solvent (SPS) system, based on 1, 8-diazabicyclo[5.4.0]undec-7-ene and decanol, which was reversibly switched on and off from heterogeneous biphasic nonpolar hydrophobic phase to homogeneous monophasic polar hydrophilic phase in an aqueous medium through exposure to an anti-solvent trigger (CO2 ) for a specific interval of time (1–10 min). Then, an SPS of polar microemulsions was switched on from a polar phase through bubbling CO2 followed by switching off to a nonpolar phase by heating in the range of 40–70 °C in the presence of N2 gas. The switching phenomenon of SPS from low polarity to high polarity was confirmed by FTIR spectrophotometry and conductivity measurements. SDLLME was successfully applied as an extracting method for the preconcentration of a hydrophobic chelate of Pb with 1-(2-pyridylazo)-2-naphthol (Pb-PAN) from a real water system. Then hydrophobic-enriched Pb-PAN-SPS was treated with a 1.5 mol L −1 HNO3 and CO2 purge for different time intervals, to switch back to its miscible polar hydrophilic monophasic state. The recovery of SPS was carried out by heating at 55 °C and purging with N2 gas. The SPS was easily recycled up to 12 times with >2% loss of efficiency of the developed method. Under the optimized experimental conditions, the limit of detection and the enhancement factor were determined to be 0.25 μg L −1 and 50, respectively.